2010
DOI: 10.1186/1471-2148-10-61
|View full text |Cite
|
Sign up to set email alerts
|

Identification of shared single copy nuclear genes in Arabidopsis, Populus, Vitis and Oryzaand their phylogenetic utility across various taxonomic levels

Abstract: BackgroundAlthough the overwhelming majority of genes found in angiosperms are members of gene families, and both gene- and genome-duplication are pervasive forces in plant genomes, some genes are sufficiently distinct from all other genes in a genome that they can be operationally defined as 'single copy'. Using the gene clustering algorithm MCL-tribe, we have identified a set of 959 single copy genes that are shared single copy genes in the genomes of Arabidopsis thaliana, Populus trichocarpa, Vitis vinifera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
339
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 292 publications
(349 citation statements)
references
References 99 publications
(149 reference statements)
9
339
0
Order By: Relevance
“…2004; Duarte et al . 2010). As orthologues of At2g13360 had only been used in a small study to demonstrate its value as a phylogenetic marker, its orthologue was identified in the genome assembly of A. alpina acc.…”
Section: Methodsmentioning
confidence: 99%
“…2004; Duarte et al . 2010). As orthologues of At2g13360 had only been used in a small study to demonstrate its value as a phylogenetic marker, its orthologue was identified in the genome assembly of A. alpina acc.…”
Section: Methodsmentioning
confidence: 99%
“…We derived 47 single-copy orthologous genes among the 11 plant species for phylogenetic analysis, taking the intersection of 344 singlecopy gene families found by OrthoMCL and 395 single-copy gene families present across diverse plant species 17 (Supplementary Table 5). …”
Section: Comparative Phylogenomics Shows Durian Paleopolyploidymentioning
confidence: 99%
“…The mtCLP complex has a homotetradecamer core consisting entirely of CLPP2 subunits that interacts with the chaperones CLPX1, 2, and 3 ( van Wijk 2015). Additionally, 50 genes with a minimum coding sequence length of 600 bp were selected at random from a published list of single-copy nuclear genes in angiosperms to test for global increases in evolutionary rates within the nuclear genome (Table S4; Duarte et al 2010). Genes that were annotated as being targeted to the mitochondria or plastids were excluded from this random set.…”
Section: Methodsmentioning
confidence: 99%
“…Genes that were annotated as being targeted to the mitochondria or plastids were excluded from this random set. The A. thaliana sequences for selected genes were obtained through the TAIR database (https://www.arabidopsis.org/) with accession numbers from the literature (Table S3 and Table S4; Peltier et al 2004;Duarte et al 2010;Olinares et al 2011;van Wijk 2015). BLAST+ 2.2.31 (Camacho et al 2009) was used to run tblastn searches (default settings) with the selected A. thaliana aa sequences as queries against each of the assembled Sileneae transcriptomes.…”
Section: Methodsmentioning
confidence: 99%